2020
DOI: 10.1111/apt.16202
|View full text |Cite
|
Sign up to set email alerts
|

Colectomy rates for ulcerative colitis in England 2003‐2016

Abstract: Summary Background Temporal trends in colectomy rate for ulcerative colitis (UC) are particularly relevant in the current era of published IBD standards and changing approach to salvage of acute severe disease. Aims To investigate temporal trends in colectomy for UC using English population data. Methods The Hospital Episode Statistics (HES) were interrogated between 2003‐2016 with two patient groups investigated independently. An ‘emergency’ cohort: emergency UC admission ≥ three days, age ≥18 and a ‘total po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“… 19 , 20 However, HES analysis of emergency admissions for UC before the pandemic has demonstrated a decrease in short‐term colectomy rate in recent years that does not persist long‐term. 20 The PROTECT‐ASUC found that the practice of gastroenterologists and colorectal surgeons had changed, with more patients receiving rescue therapy in the form of biologicals, ciclosporin or tofacitinib. 17 This study suggests the trend to delay colectomy for patients undergoing emergency admission for ulcerative colitis has been exacerbated due to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 19 , 20 However, HES analysis of emergency admissions for UC before the pandemic has demonstrated a decrease in short‐term colectomy rate in recent years that does not persist long‐term. 20 The PROTECT‐ASUC found that the practice of gastroenterologists and colorectal surgeons had changed, with more patients receiving rescue therapy in the form of biologicals, ciclosporin or tofacitinib. 17 This study suggests the trend to delay colectomy for patients undergoing emergency admission for ulcerative colitis has been exacerbated due to the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that colectomy rate is decreasing in the era of access to biologic medications 19,20 . However, HES analysis of emergency admissions for UC before the pandemic has demonstrated a decrease in short‐term colectomy rate in recent years that does not persist long‐term 20 . The PROTECT‐ASUC found that the practice of gastroenterologists and colorectal surgeons had changed, with more patients receiving rescue therapy in the form of biologicals, ciclosporin or tofacitinib 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We confirmed that steroid dependency could be avoided through the use of biological agents in patients with high-severity UC (Figure 3 ). Since colectomy, like the length of the steroid-free period, is an important factor when evaluating long-term outcomes, other studies have also reported on colectomy rates according to treatment[ 37 - 39 ]. In this study, only 1 patient in Group A underwent colectomy due to uncontrolled hematochezia, so it was not possible to compare colectomy as a long-term outcome.…”
Section: Discussionmentioning
confidence: 99%
“…However, remission rates range between 30% and 40% with most advanced therapies and data suggest that colectomy rates are not decreasing despite biologics. 119 A prospective population-based cohort study has also shown similar 5-year surgery, hospitalisation and disease progression rates compared to cohorts from 20 years ago, despite earlier biologic therapy. 120 Taken together with the complex, incompletely understood and evolving immunobiology of IBD, it highlights a major unmet need for other therapeutic targets to abrogate the inflammatory response.…”
Section: What Is In the Pipeline And What Is Comingmentioning
confidence: 93%